Translating, transmitting and transforming Waldorf curricula: one hundred years after the first published curriculum in 1925 - Rawson, Martyn (Frontiers in Education, 2024)
The first Waldorf School was founded in 1919 and the first curriculum was published in German in1925. Since then, this curriculum has been translated into many other languages and transmitted across geographical space to other cultural contexts whilst maintaining the character of Steiner Waldorf education. For much of the past one hundred years it has been a taken-for-granted source of inspiration for Waldorf teachers. However, Waldorf education faces a number of challenges to its curriculum. In many countries it is increasingly forced to explain and justify itself to the state and comply with educational policy requirements for standardization and testing. It is challenged to adapt to the digital age and it faces calls to modify its original Western focus and become more attuned to local cultures, whilst retaining its universal humanist aspirations and its intrinsic character and function.Given that the curriculum is one of the best-known features of Waldorf education, it is surprising that there has been so little research on it. Drawing on the relevant literature, this review paper explores the fundamental concepts of curriculum within Waldorf education: its primary characteristics and functions. It tracks the historical development and the way the curriculum has been adapted both to requirements within schools and to external factors. Along the way there have been differing understandings of the status and function of the curriculum, including whether and in what sense it is universal and essentially unchangeable and/or how it can be adapted. This paper highlights a number of areas in which further research is needed and reports on important new developments, which promise to sustain the viability and relevance of the Waldorf curricula.